(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Numeracy is very important for students to master in the 21st century. Numeracy means applying numerical and mathematical concepts. The fact that the applied learning is still not effective at SDN Gayungan II/423 Surabaya. The purpose of this study was to find out that there was no effect of domino card-assisted Problem Based Learning on student numeracy. This type of research uses quantitative research with experimental methods. The design of this study was a nonequivalnt posttest-only control design. The population in this study were all grade III students at SDN Gayungan II/423 Surabaya, totaling 44 students. Through cluster random sampling, a sample of class III B was selected as the experimental class and class III A as the control class. Data collection techniques through tests. The data analysis technique used is a statistical test consisting of a normality test, homogeneity test, and hypothesis testing using the t-test. The results of the study showed that there was an influence of Problem Based Learning assisted by domino cards on the numeracy of class III SDN Gayungan II/423 Surabaya.